Impact of impaired cerebral blood flow autoregulation on cognitive impairment - Wang, Shaoxun; Tang, Chengyun; Liu, Yedan; Border, Jane J.; Roman, Richard J.; Fan, Fan (Frontiers in Aging, 2022)
Although the causes of cognitive impairment are multifactorial, emerging evidence indicates that cerebrovascular dysfunction plays an essential role in dementia. One of the most critical aspects of cerebrovascular dysfunction is autoregulation of cerebral blood flow (CBF), mainly mediated by the myogenic response, which is often impaired in dementia individuals with comorbidities, such as diabetes and hypertension. However, many unsolved questions remain. How do cerebrovascular networks coordinately modulate CBF autoregulation in health and disease? Does poor CBF autoregulation have an impact on cognitive impairment, and what are the underlying mechanisms? This review summarizes the cerebral vascular structure and myogenic (a three-phase model), metabolic (O2, CO2, adenosine, and H+), and endothelial (shear stress) factors in the regulation of CBF; and the consequences of CBF dysautoregulation. Other factors contributing to cerebrovascular dysfunction, such as impaired functional hyperemia and capillary abnormalities, are included as well. Moreover, this review highlights recent studies from our lab in terms of novel mechanisms involved in CBF autoregulation and addresses a hypothesis that there is a three-line of defense for CBF autoregulation in the cerebral vasculature.